Association between early life weight gain and abdominal fat partitioning at 4.5 years is sex-, ethnicity- and age-dependent - Sadananthan, Suresh Anand (Obesity (Silver Spring), 2019)
OBJECTIVE: To investigate the independent associations between age-specific annual weight gain from birth to age 4 years and fat deposition in metabolically distinct compartments at age 4.5 years in a South Asian longitudinal birth cohort. METHODS: Volumetric abdominal MRI with comprehensive segmentation of deep (DSAT) and superficial subcutaneous (SSAT), and visceral adipose tissues (VAT) was performed in 316 children (150 boys, and 166 girls in three ethnic groups: 158 Chinese, 94 Malay, and 64 Indian) aged 4.5 years. Associations between fat volumes and annual relative weight gain conditional on past growth were assessed overall and stratified by sex and ethnicity. RESULTS: Conditional relative weight gain had stronger associations with greater SAT and VAT at age 4.5 years in girls than boys, and in Indians compared with Malay and Chinese. Overall, the magnitude of association was the largest during 2-3 years for SAT, and 1-2 years for VAT. Despite similar body weight, Indian children, and girls had the highest DSAT and SSAT volumes at age 4.5 years (all p-interaction<0.05). No significant sex or ethnic differences were observed in VAT. With increasing BMI, Indian children had the highest tendency to accumulate VAT, and girls accumulated more fat than boys in all depots (all p-interaction<0.001). CONCLUSIONS: Indian ethnicity and female sex predisposed children to accumulate more fat in the visceral adipose depot with increasing conditional relative weight gain in the second year of life. Thus, 1-2 years age may be a critical window for interventions to reduce visceral fat accumulation.